Predictive factors for HIV infection among men who have sex with men and who are seeking PrEP: a secondary analysis of the PROUD trial. (27th March 2019) - White, Ellen; Dunn, David T; Desai, Monica; Gafos, Mitzy; Kirwan, Peter; Sullivan, Ann K; Clarke, Amanda; McCormack, Sheena
Abstract : Objectives: Pre-exposure prophylaxis (PrEP) is a highly effective method of HIV prevention for men who have sex with men (MSM). However, uncertainty remains around the optimal eligibility criteria for PrEP, specifically whether there are subgroups at low risk of HIV for whom PrEP might not be warranted. Methods: PROUD was an open-label waitlist trial design that randomised MSM attending participating sexual health centres in England to receive PrEP immediately (IMM) or after a deferral period of 1 year (DEF). This analysis is based on participants who were randomised to the deferred arm, when they did not have access to PrEP. HIV incidence was compared between subgroups defined by baseline characteristics. Results: Overall, 21 participants acquired HIV infection over 239.3 person-years (PY) follow-up, yielding an incidence rate of 8.8/100 PY (95% CI 5.4 to 13.4). Two highly significant predictors for HIV acquisition were identified. Men with a self-reported diagnosis of syphilis, rectal chlamydia (CT) or rectal gonorrhoea (GC) in the previous 12 months had an incidence of 17.2/100 PY (95% CI 9.7 to 28.5); those reporting receptive anal intercourse without a condom (ncRAI) with two or more partners in the previous 3 months had an incidence of 13.6/100 PY (95% CI 7.9 to 21.7). The incidence rate among participants lacking both of these risk factors was 1.1/100 PY (1/87.6, 95% CI 0.03 to 6.4). Conclusions: The high HIV incidence in PROUD suggests that most participants appropriately judged their need for PrEP. Eligibility criteria for a PrEP programme can therefore be broad, as in the current guidelines. However, a recent history of syphilis or rectal CT/GC, or multiple ncRAI partners indicates a high imminent risk of HIV infection. MSM with any of these characteristics should be offered PrEP as a matter of urgency.